Blockchain in real estate : theoretical advances and new empirical applications - Jreisat, Ammar; Mili, Mehdi (Palgrave Macmillan, 2024)
This book provides an overview of real estate blockchain technology and its applications. It explores blockchain across industries, cryptocurrencies' impact on payment systems, money transfers, investment, and venture capital. It highlights the need for trust in digital technologies as companies reevaluate operations. The book discusses how blockchain enables secure property and land ownership management through verified transaction histories and immutable records. It also examines how smart contracts enhance property management efficiency. Blockchain has the potential to revolutionize the traditional Multi-Listing System (MLS) in real estate. By creating a transparent MLS, brokers and agents can access the complete transaction history of properties. Blockchain can also streamline registries, titles, and transactions by certifying ownership transfers and confirming financial data. However, there are regulatory and administrative challenges to overcome. Once implemented, blockchain could simplify and speed up buying and profiting from real estate globally. This book explores the implications of real estate blockchain and the opportunities and challenges. It will interest scholars, researchers, and real estate, finance, and financial technology students, real estate agents, town planners, developers, real estate experts, investors, communities. Ammar Barham Jreisat holds a Ph.D. in Finance from Western Sydney University, Australia. He is an Assistant Professor of Finance and Program Coordinator of the M.Sc. in Real Estate Development and Property Management at the University of Bahrain. He is an Associate Editor, and reviewer, and has won awards from MEEA and ERF. He has published peer-reviewed articles in leading international conference proceedings and journals. His research interests include Finance, Banking, Financial Markets, and efficiency and productivity measurement. Mehdi Mili, Ph.D., is an Associate Professor at the University of Bahrain. He received his master's in finance and PhD in Finance from the University of Sfax, Tunisia, and the University of Poitiers, France. His research interests include fixed-income modelling, interest rate risk management, and structured products. Mehdi is a conference speaker, and his research has been published in international journals and funded by the University of Sfax and the University of Bahrain.